Xerophthalmia in picky eater children - Aiman Ifwat Samsolbari; On, Heong Liew; Hanisah Abdul Hamid; Sylves Patrick; Shuaibah Ab Ghani (Cureus, Inc., 2022)
Xeropthalmia refers to a range of ocular symptoms caused by vitamin A deficiency (VAD), ranging from night blindness and Bitot's spots to corneal xerosis, ulceration, and keratomalacia, which can lead to blindness. We report two cases of xerophthalmia in children with intellectual disabilities. Ocular examination revealed generalized conjunctival xerosis, corneal xerosis, and dense superficial punctate keratopathy. Both share a history of a strict self-selective diet of mainly rice and noodles. Serum vitamin A levels for these children showed a very low level (<0.10 µmol/L) and were categorized as severe VAD. One of the cases showed signs of improvement, and the other one succumbed to death secondary to pneumonia. Therefore, proper history-taking, early detection, and prompt treatment are important to prevent the devastating sequelae of VAD.